2015
DOI: 10.1016/j.cct.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Brain function predictors and outcome of weight loss and weight loss maintenance

Abstract: Obesity rates are associated with public health consequences and rising health care costs. Weight loss interventions, while effective, do not work for everyone, and weight regain is a significant problem. Eating behavior is influenced by a convergence of processes in the brain, including homeostatic factors and motivational processing that are important contributors to overeating. Initial neuroimaging studies have identified brain regions that respond differently to visual food cues in obese and healthy weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…The present investigation is an analysis from the first 3 months (12 weeks) of a 9‐month study. A detailed description of the materials and methods for this study can be found in Szabo‐Reed et al This study consisted of a 12‐week diet followed by a 6‐month maintenance period. Functional magnetic resonance imaging (fMRI) scans were completed on participants with obesity (BMI 30 to 45 kg/m 2 ) with a visual food cue reactivity fMRI paradigm in a baseline session before participants entered the weight management program.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The present investigation is an analysis from the first 3 months (12 weeks) of a 9‐month study. A detailed description of the materials and methods for this study can be found in Szabo‐Reed et al This study consisted of a 12‐week diet followed by a 6‐month maintenance period. Functional magnetic resonance imaging (fMRI) scans were completed on participants with obesity (BMI 30 to 45 kg/m 2 ) with a visual food cue reactivity fMRI paradigm in a baseline session before participants entered the weight management program.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline demographics and sample characteristics are included in Table . All inclusion and exclusion criteria have been previously detailed elsewhere . Briefly, participants were included in the study if they met the following inclusion criteria: (1) age 21 to 55 years, (2) BMI of ≥30.0 to 45.0 kg/m 2 , and (3) clearance for participation from their primary care physician.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of this investigation have been previously published ; therefore, a brief description of the methods has been provided.…”
Section: Methodsmentioning
confidence: 99%